The relationships between burnout, general wellbeing, and psychological detachment with turnover intention in Chinese nurses: a cross-sectional study - Zhang, Fengzhi; Lin, Chunhui; Li, Xiaoxue; Li, Manman; Jia, Ruolin; Guo, Xiaoli; Bai, Hua (Frontiers in Public Health, 2023)
Background: It is critical to minimize nurse turnover to improve the quality of care and patient safety. In-depth investigation is required to better understand the factors related to nurses' turnover intentions. Aim: This study determined the relationships of burnout, general well-being, psychological detachment with turnover intention among nurses in China. Methods: A cross-sectional survey using convenience sampling was conducted in one hospital in China between January 2023 and March 2023. A total of 536 nurses were surveyed using the General Well-Being Schedule (GWB), the Maslach Burnout Inventory scale (MBI), the Psychological Detachment scale, and the Turnover Intention scale. The collected data were analyzed using SPSS 26.0 statistical software. The chi-square test and binary logistic regression analysis were used to explore the factors related to turnover intention. Results: Our data demonstrated that the turnover intention scores were 13 (10, 15.75), with 56% of nurses exhibiting a high level of turnover intention. Binary logistic regression analysis results indicated that being on a contract (OR=4.385, 95%CI=2.196-8.754), working in the pediatrics (OR=2.392, 95%CI=1.267-4.514) or obstetrics (OR=2.423, 95%CI=1.145-5.126) department, and experiencing burnout (OR=1.024, 95%CI=1.008-1.041) were associated with a heightened level of turnover intention. Conversely, organizational satisfaction (OR=0.162, 95%CI=0.033-0.787) and general well-being (OR=0.967, 95%CI=0.946-0.989) were identified as factors that hindered the intention to leave. Conclusion: Findings from this study suggest that nurses employed on a contract basis, working in pediatric or obstetric departments, expressing dissatisfaction with the organization, reporting low general well-being, and experiencing high levels of burnout require special attention. The identification of these risk factors can inform targeted interventions and support programs aimed at improving the well-being and retention of nurses in these settings.